Sol Brain, Pre-Operative Magnetic Resonance Spectroscopy and Surgical Biopsy Yield - Bangash, Khurshid Ali; Yousaf, Nasrin; Ilyas, Sohail; Mahmood, Rashid; Parveen, Ishrat; Yousaf, Ajmal; Khushdil, Arshad; Nathaniel, Sharoon (Pakistan Armed Forces Medical Journal, 2023)
Objective: To ascertain the positive predictive value (PPV) of magnetic resonance spectroscopy (MRS) in diagnosing neoplastic intracranial masses by taking histopathology as a benchmark.Study Design: Cross-sectional study.Place and Duration of Study: Combined Military Hospital, Rawalpindi Pakistan, from Jan 2019 to Jun 2021.Methodology: After approval from the Ethical Review Committee, 64 patients with neoplastic intracranial mass lesions on MRI were incorporated into the study. Patients with a history of brain surgery done previously, breastfeeding females, claustrophobia, already diagnosed type of tumour, and contraindication to MRI were excluded. MR Spectroscopy was performed, and findings were correlated with histopathology.Results: Of 64 patients, 39(60.94%) were males, and 25(39.06%) were females. Magnetic Resonance Spectroscopy (MRS) supported the diagnosis of neoplastic brain lesions in all 64 patients. Histopathology confirmed malignant brain lesions in 59 cases, whereas 05 cases had benign lesions. PPV of MRS in the diagnosis of neoplastic brain lesions was 92.19%.Conclusion: This study concluded that MRS is a non-invasive option having a very good PPV in determining neoplastic brain lesions.